Use of Rice Husk-Bark Ash in Producing Self-Compacting Concrete - Sumrerng Rukzon; Prinya Chindaprasirt (Advances in Civil Engineering)
This paper presents the use of blend of Portland cement with rice husk-bark ash in producing self-compacting concrete (SCC). CT was partially replaced with ground rice husk-bark ash (GRHBA) at the dosage levels of 0%–40% by weight of binder. Compressive strength, porosity, chloride penetration, and corrosion of SCC were determined. Test results reveal that the resistance to chloride penetration of concrete improves substantially with partial replacement of CT with a blend of GRHBA and the improvement increases with an increase in the replacement level. The corrosion resistances of SCC were better than the CT concrete. In addition, test results indicated that the reduction in porosity was associated with the increase in compressive strength. The porosity is a significant factor as it affects directly the durability of the SCC. This work is suggested that the GHRBA is effective for producing SCC with 30% of GHRBA replacement level.